Language and Power Dynamics in Automobile Advertising: A Multimodal Discourse Analysis of Word Choice and Semiotics - Wasif Hussain; Panggabean, Himpun (Journal of Applied Linguistics, 2024)
Concepts including communication patterns in public institutions, media discourse (reports, commercials, television broadcasts, etc.), and the construction of individual and group identities that communicate ideological views, authority, and status are all of importance to critical discourse analysis (CDA). Ad discourse is one of the media discourses that this study uses. The three most well-known and valuable brands that the researcher selected were Toyota, Mercedes-Benz, Audi, Land Rover, and BMW. This study's objective is to use semiotic analysis and CDA to analyze the data. Within the technique, the researcher employed a qualitative approach. The findings revealed that each brand crafts a unique narrative, leveraging advanced technology, aesthetic appeal, and emotional resonance to maintain a strong market presence. These advertisements are more than just promotional tools; they are meticulously designed works of art that reflect the evolving consumer preferences and competitive dynamics of the automotive industry. The study underscored the importance of strategic messaging in automotive advertising, demonstrating how these brands effectively capture and retain consumer interest through diverse and dynamic marketing approaches. Keywords : Critical discourse_analysis; Semiotic_analysis; Automobile_advertising